A patient decision aid for breast cancer patients deciding on their radiation treatment, no change in decisional conflict but better informed choices. (December 2021) - Raphael, D.B.; Russell, N.S.; Winkens, B.; Immink, J.M.; Westhoff, P.G.; Stenfert Kroese, M.C.; Stam, M.R.; Bijker, N.; van Gestel, C.M.J.; van der Weijden, T.; Boersma, L.J.
Highlights: No difference was found in decisional conflict with or without PtDA use. Patients who used the PtDA had more knowledge, suggesting a better informed choice. Patients who used the PtDA chose more often for a less intensive treatment. The use of the PtDA was not significant associated with a longer consultation time. Abstract: Background and Purpose: In selected breast cancer patients, radiation treatment (RT) lowers the recurrence risk, with minor or no improvement of survival. In these patients, the choice to undergo RT is considered a preference-sensitive decision. To facilitate shared decision-making (SDM) for this choice, a patient decision aid was made. We aimed to evaluate the effect of the PtDA on decisional conflict. Material and methods: We performed a multi-center pre- and post-intervention study (BRASA-trial). The first 214 patients made a choice without support of the PtDA; the subsequent 189 patients received a link to the PtDA. The primary endpoint was decisional conflict; secondary endpoints were perceived SDM and knowledge on treatment options. Patients filled out questionnaires immediately after, and three months after their decision. Data were analyzed with multi-level regression analysis. Results: After correcting for the difference in age and educational level, the mean (±SD) decisional conflict for the intervention group (27.3 ± 11.4) was similar to the control group (26.8 ± 11.4; difference = 0.86, 95 %CI 1.67, 3.36) three months after their decision. This also applied to perceived SDM. Patients exposed to the PtDA pursued additional treatment less often (45% vs 56%, odds ratio 0.59, 95 %CI 0.37, 0.95) and scored significantly higher on the knowledge test (7.4 ± 2.5 vs 6.1 ± 2.7, corrected difference = 1.0, 95 %CI 0.50, 1.49). There was no significant increase in consultation time. Conclusions: Handing out the PtDA was not associated with improved scores in decisional conflict or perceived SDM, but it was associated with a choice for less additional treatment and better knowledge about the treatment options.